Real time implementation of the BESS to smoothen the output power fluctuation of the variable speed wind turbine generator - Sattar, A.; Al Durra, A.; Caruana, C.; Muyeen, S.M.; Tamura, J. (2012)
In this paper, a grid connected variable speed wind turbine (VSWT) PMSG integrated with the NaS type battery energy storage system (BESS) is modeled in the Real Time Digital Simulator (RTDS) to analyze the performance in the real system. This work is also a part of the future power hardware-in-loop (PHIL) test; therefore, individual components are modeled considering the practical viewpoints. Wind turbine, power grid and control system are modeled in the large time-step main network, however, wind generator (PMSG), frequency converter (FC), BESS integrated with STATCOM are modeled in the RTDS VSC small time-step network to adopt with the higher switching frequencies. Interface transformer is used to connect the different time-step sub network. Option of integrating the anemometer is kept open for future PHIL test. Simulation results are compared with the laboratory standard power system software PSCAD/EMTDC to validate the model developed in the RTDS/RSCAD.